The Urban Elements’ Visual Attractiveness of Tugu Pal Putih as Yogyakarta City Tourist Spot - Agus S. Sadana (International Journal of Glocal Tourism, 2021)
Purpose: This study aims to determine the attractiveness of Tugu (Tugu Pal Putih) as a leading tourist attraction in the current situation of Yogyakarta City space. Research methods: Tugu Pal Putih is at the main road intersection of Yogyakarta City, Indonesia. It has tangible and intangible aspects developed as a research instrument. Data was collected quantitatively using a questionnaire that was compiled based on the characteristics of the object using the semantic differential technique and calculated using Microsoft Excel software. Findings: The vigorous concept of the Tugu as a part of the philosophical axis of Yogyakarta can strengthen the tourists' minds and needs to increase its capacity to give the tourists an experience to feel the philosophical axis. Implications: The study has a beneficial impact on planning the tourists' flow in observing the Tugu. It needs the maintenance of existence as a Yogyakarta cultural symbol and a valuable world cultural heritage that is amazing for tourism